Posttraumatic Stress Disorder and Orofacial Pain - Davor Vagić; Natalija Prica; Dražen Shejbal (University of Zagreb. School of Dental Medicine, 2015)
Chronic orofacial pain occurs frequently in patients with posttraumatic stress disorder (PTSD) and at the same time any pathological process involving orofacial area can be reflected in emotional interpretation of pain and can trigger a series of reactions associated with the PTSD group of symptoms in patients with PTSD. Painful stimuli caused in this way may occur after the primary cause ceased, and because of convergence can cause referred pain outside of the anatomical site where the primary injury occurred. Chronic orofacial pain and PTSD are diagnosed on the basis of subjective testimony and this regularly occurs in the context of social interaction between patients, doctors, medical staff or researchers making it difficult to standardize the results and introduces many cultural phenomena.